Heat shock protein 90 targets a chaperoned peptide to the static early endosome for efficient cross‐presentation by human dendritic cells. Issue 1 (15th December 2014) - Tanaka, Tsutomu; Okuya, Koichi; Kutomi, Goro; Takaya, Akari; Kajiwara, Toshimitsu; Kanaseki, Takayuki; Tsukahara, Tomohide; Hirohashi, Yoshihiko; Torigoe, Toshihiko; Hirata, Koichi; Okamoto, Yoshiharu; Sato, Noriyuki; et al.
<x xml:space="preserve">Abstract</x> The presentation of an exogenous antigen in a major histocompatibility complex class‐I‐ restricted fashion to CD8+ T cells is called cross‐presentation. Heat shock proteins (HSPs) such as Hsp70, gp96, and Hsp90 have been shown to elicit efficient CTL responses by cross‐presentation through an as‐yet entirely unknown mechanism. Hsp90 is the most abundant cytosolic HSP and is known to act as a molecular chaperone. We have shown that a tumor antigen peptide complexed with Hsp90 could be cross‐presented by dendritic cells (DCs) through an endosomal pathway in a murine system. However, it has not been determined whether human DCs also cross‐present an Hsp90–peptide complex and induce peptide‐specific CTLs. In this study, we found that an Hsp90–cancer antigen peptide complex was efficiently cross‐presented by human monocyte‐derived DCs and induced peptide‐specific CTLs. Furthermore, we observed that the internalized Hsp90–peptide complex was strictly sorted to the Rab5+, EEA1+ static early endosome and the Hsp90‐chaperoned peptide was processed and bound to MHC class I molecules through an endosome‐recycling pathway. Our data indicate that targeting of the antigen to a "static" early endosome by Hsp90 is essential for efficient cross‐presentation.